Interdisciplinary full mouth rehabilitation of a patient with amelogenesis imperfecta from childhood to young adult‐hood: A 12‐year case report - Élisa Caussin; Frédéric Courson; Elisabeth Dursun; Yohann Brukarz; Daniel Dot; Catherine Chaussain; Jean‐Pierre Attal; Philippe François (Clinical Case Reports, 2024)
Key Clinical Message Treatment of patients with amelogenesis imperfecta extends over many years, from childhood to early adulthood. Their management at any age is complex and has to be adapted in relation to therapies validated in the general population.